Peningkatan Mutu Pendidikan melalui Proses Pendampingan Belajar Mengajar di Desa Tampalang - imam Permana; Fitriani (PPM LP2M UIN Alauddin Makassar, 2023)
Education is the most important thing in life. Every human being has the right to receive and hopes to always develop in education. Education means that it is a life process in developing each individual to be able to live and live life. In 2019, there was an increasingly endless pandemic which caused obstacles to all sectors of life, including the education sector. Likewise in Indonesia, the rise of Covid-19 resulted in face-to-face learning being diverted to online learning which took almost two years. And finally, in September 2021 face-to-face learning will be held again with a limited number of students and still complying with health protocols. This service activity aims to provide learning assistance for elementary school age students through a work program (teaching and learning) in Tampalang Village. The method used is the teaching and learning method in general with an effort to produce potential students in the future. Based on the learning outcomes, the students looked enthusiastic in learning and the knowledge gained by the students increased. It is hoped that one day the knowledge gained can be useful and useful for everyone. So that it is expected to print brilliant generations.